Dynamic recrystallization model of the Cu–Cr–Zr–Ag alloy under hot deformation. Issue 9 (15th April 2016) - Zhang, Yi; Tian, Baohong; Volinsky, Alex A.; Chen, Xiaohong; Sun, Huili; Chai, Zhe; Liu, Ping; Liu, Yong
Abstract: Abstract : Hot deformation and dynamic recrystallization (DRX) behavior of the Cu–Cr–Zr–Ag alloy were studied by hot compressive tests in the 650–950 °C temperature and 0.001–10 s −1 strain rate ranges using Gleeble-1500D thermomechanical simulator. The activation energy of deformation was determined as Q = 343.23 kJ/mol by the regression analysis. The critical conditions, including the critical strain and stress, for the occurrence of DRX were determined based on the alloy strain hardening rate. The critical strain related to the onset of DRX decreases with temperature. The ratios of the critical to peak stress and critical to peak strain were also identified as 0.91 and 0.49, respectively. The evolution of DRX microstructure strongly depends on the deformation conditions in terms of temperature and strain rate. Dislocation generation and multiplication are the main hot deformation mechanisms for the alloy. The addition of Ag can refine the grain and effectively improve the DRX of the Cu–Cr–Zr alloy. It can also inhibit the growth of the DRX grains at 950 °C deformation temperature, making the microstructure much more stable.